P11.07 LAPTM5 functions as a tumor suppressor via CD40 - NFêB pathway inhibition and represents a potential biomarker for temozolomide sensitivity in CD40 proficient glioblastoma. (6th September 2019) - Berberich, A; Bartels, F; Tang, Z; Pusch, S; Hucke, N; Kessler, T; Dong, Z; Wiestler, B; Winkler, F; Platten, M; Wick, W; Abdollahi, A; et al.
Abstract: BACKGROUND: Glioma therapy is challenged by the invasive nature of glioma resulting in tumor recurrence and treatment resistance. Lysosomal protein transmembrane 5 ( LAPTM5 ) was identified to inhibit invasion by screening for invasion-associated genes in glioma. The aim of this study was to decipher the function of LAPTM5 in glioblastoma and its interaction with the CD40 receptor which was shown to be highly expressed in up to 40% of glioblastoma. METHODS: LAPTM5 expression was correlated with clinical outcome of glioma patients. Knockdown of LAPTM5 was performed in different glioma cell lines to analyze the impact on clonogenicity, invasiveness, sensitivity to temozolomide chemotherapy and tumorigenicity in-vitro and in-vivo in a subcutaneous xenograft mouse model. Expression array was used to elucidate the underlying pathways. CD40 knockdown and overexpression was induced to prove the crosstalk of LAPTM5 and CD40. RESULTS: LAPTM5 expression correlated with better overall survival in high grade glioma patients and acted as a tumor suppressor in CD40 positive glioblastoma cells. LAPTM5 inhibited CD40-mediated NFκB activation resulting in anti-invasive, anti-clonogenic and temozolomide sensitizing effects in-vitro and in-vivo. Vice-versa, knockdown of LAPTM5 enhanced tumorigenicity by activation of the NFκB pathway which was overcome by NFκB inhibition. Importantly, CD40 expression was required for LAPTM5 -mediated tumor suppressive activity. CONCLUSION: LAPTM5 conveyed tumor suppressive and temozolomide sensitizing effects in CD40-positive glioblastoma by inhibition of CD40-mediated NFκB activation and thereby might provide a reasonable biomarker for sensitivity to temozolomide in CD40-positive glioblastoma.